ANALYSIS OF ENGLISH TEXTBOOK WITH TITLE “ BAHASA INGGRIS “ USED IN ELEVENTH GRADE SENIOR HIGH SCHOOL IN 2013 CURRICULUM - Risca Nur Qodaria (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2023)
JOLE (Journal of Language Education), Vol 7 No.1 May 2023English Education Study Program, Universitas Baturaja30ANALYSIS OF ENGLISH TEXTBOOK WITH TITLE “ BAHASAINGGRIS “ USED IN ELEVENTH GRADE SENIOR HIGHSCHOOL IN 2013 CURRICULUMRisca Nur QodariaBaturaja Universityriscanurqa11@gmail.comABSTRACTThe objectives of this study are to find out the suitability of impressionistic and in-depth analysis in thetextbook entitles